Spontaneous Resistance of Erwinia amylovora Against Bacteriophage Y2 Affects Infectivity of Multiple Phages - Knecht, Leandra E.; Born, Yannick; Pelludat, Cosima; Pothier, Joël F.; Smits, Theo H. M.; Loessner, Martin J.; Fieseler, Lars (Frontiers in Microbiology, 2022)
Broad application of antibiotics gave rise to increasing numbers of antibiotic resistant bacteria. Therefore, effective alternatives are currently investigated. Bacteriophages, natural predators of bacteria, could work as such an alternative. Although phages can be highly effective at eliminating specific bacteria, phage resistance can be observed after application. The nature of this resistance, however, can differ depending on the phage. Exposing Erwinia amylovora CFBP 1430, the causative agent of fire blight, to the different phages Bue1, L1, S2, S6 or M7 led to transient resistance. The bacteria reversed to a phage sensitive state after the phage was eliminated. When wild type bacteria were incubated with Y2, permanently resistant colonies (1430Y2R) formed spontaneously. In addition, 1430Y2R revealed cross-resistance against other phages (Bue1) or lowered the efficiency of plating (L1, S2, S6). Pull down experiments revealed that Y2 is no longer able to bind to the mutant suggesting mutation or masking of the Y2 receptor. Other phages tested were still able to bind to 1430Y2R. Bue1 was observed to still adsorb to the mutant, but no host lysis was found. These findings indicated that, in addition to the alterations of the Y2 receptor, the 1430Y2R mutant might block phage attack at different stage of infection. Whole genome sequencing of 1430Y2R revealed a deletion in the gene with the locus tag EAMY_2231. The gene, which encodes a putative galactosyltransferase, was truncated due to the resulting frameshift. The mutant 1430Y2R was monitored for potential defects or fitness loss. Weaker growth was observed in LB medium compared to the wild type but not in minimal medium. Strain 1430Y2R was still highly virulent in blossoms even though amylovoran production was observed to be reduced. Additionally, LPS structures were analysed and were clearly shown to be altered in the mutant. Complemention of the truncated EAMY_2231 in trans restored the wild type phenotype. The truncation of EAMY_2231 can therefore be associated with manifold modifications in 1430Y2R, which can affect different phages simultaneously.